Smart products, smarter services : strategies for embedded control - Cronin, Mary J. (New York : Cambridge University Press, 2010)
'Billions of smart connected products are changing the competitive landscape for business and the daily lives of consumers. This book analyzes the evolution of embedded product intelligence and the impact of smart products on the automotive, wireless, energy, residential and health industries. It considers the transformation of consumer ownership models and privacy issues when smart products continuously monitor consumer behavior. Smart Products, Smarter Services recommends strategies for creating profitable smart ecosystems, product platforms and services'--
Includes bibliographical references and index.
Keywords: Embedded computer systems; Computer storage devices; Consumer goods; Electronic commerce